Oxidative Stress Modulation and Glutathione System Response During a 10-Day Multi-Stressor Field Training - Liāna Pļaviņa; Edgars Edelmers (Journal of Functional Morphology and Kinesiology)
Objectives: To evaluate how a 10-day multi-stressor field-training course—combining high physical and psycho-emotional demands, caloric restriction, and severe sleep deprivation—affects systemic oxidative/antioxidative status and biomarkers of nucleic-acid and skeletal-muscle damage in trained military cadets. Methods: Seventy-five healthy cadets (8 women, 67 men; 22–34 y) completed the course. Standardised operational rations (700–800 kcal day−¹) and two 20 min tactical naps per 24 h were enforced. Pre- and post-course venous blood was collected after an overnight fast. Plasma superoxide-dismutase activity (SOD), reduced and oxidised glutathione (GSH, GSSG), malondialdehyde (MDA), and hydrogen peroxide (H₂O₂) were quantified by colourimetric/fluorometric assays; 8-hydroxy-2-deoxyguanosine (8-OHdG) and myoglobin were measured by ELISA. The oxidative-stress index (OSI) was calculated as GSSG·GSH−¹. Within-subject differences were assessed with Wilcoxon signed-rank tests; associations between biomarker changes were explored by Spearman correlation. Results: After training, GSH (+175%, p < 0.001) and GSSG (+32%, p < 0.001) rose significantly, whereas SOD (−19%, p = 0.002), H₂O₂ (−20%, p = 0.015), MDA (−50%, p < 0.001), 8-OHdG (−23%, p < 0.001), and OSI (−47%, p < 0.001) declined. Myoglobin remained unchanged (p = 0.603). Reductions in MDA correlated inversely with increases in GSSG (rₛ = −0.25, p = 0.041), while H₂O₂ changes correlated positively with GSSG (rₛ = 0.25, p = 0.046), indicating a glutathione-driven adaptive response. Conclusions: Ten consecutive days of vigorous, calorie- and sleep-restricted field training elicited a favourable redox adaptation characterised by enhanced glutathione-mediated antioxidant capacity and lower circulating oxidant concentrations, without evidence of DNA or skeletal-muscle damage. The data suggest that, in physically prepared individuals, prolonged multi-stressor exposure can strengthen endogenous antioxidant defences rather than precipitate oxidative injury.